Daily Thermal Fluctuations Experienced by Pupae via Rhythmic Nursing Behavior Increase Numbers of Mushroom Body Microglomeruli in the Adult Ant Brain - Falibene, Agustina; Roces, Flavio; Rössler, Wolfgang; Groh, Claudia (Frontiers in Behavioral Neuroscience, 2016)
Social insects control brood development by using different thermoregulatory strategies. Camponotus mus ants expose their brood to daily temperature fluctuations by translocating them inside the nest following a circadian rhythm of thermal preferences. At the middle of the photophase brood is moved to locations at 30.8°C; 8 h later, during the night, the brood is transferred back to locations at 27.5°C. We investigated whether daily thermal fluctuations experienced by developing pupae affect the neuroarchitecture in the adult brain, in particular in sensory input regions of the mushroom bodies (MB calyces). The complexity of synaptic microcircuits was estimated by quantifying MB-calyx volumes together with densities of presynaptic boutons of microglomeruli (MG) in the olfactory lip and visual collar regions. We compared young adult workers that were reared either under controlled daily thermal fluctuations of different amplitudes, or at different constant temperatures. Thermal regimes significantly affected the large (non-dense) olfactory lip region of the adult MB calyx, while changes in the dense lip and the visual collar were less evident. Thermal fluctuations mimicking the amplitudes of natural temperature fluctuations via circadian rhythmic translocation of pupae by nurses (amplitude 3.3°C) lead to higher numbers of MG in the MB calyces compared to those in pupae reared at smaller or larger thermal amplitudes (0.0, 1.5, 9.6°C), or at constant temperatures (25.4, 35.0°C). We conclude that rhythmic control of brood temperature by nursing ants optimizes brain development by increasing MG densities and numbers in specific brain areas. Resulting differences in synaptic microcircuits are expected to affect sensory processing and learning abilities in adult ants, and may also promote interindividual behavioral variability within colonies.